Neurological Sequela of Acute Pesticide Poisoning Among Adults in Central Taiwan - Chen, Yen-Chung; Lin, Chin-Hsien; Wu, Shey-Lin (Frontiers in Neurology, 2021)
Background and Purpose: Cases of acute pesticide poisoning account for significant morbidity and mortality in developing countries; however, its burden in Taiwan remains unknown. The study examined acute pesticide poisoning (APP) involving adults in the central region of Taiwan, which is a mainly agricultural sub-urban area. Methods: The retrospective study evaluated the outcome and neurological sequelae of patients with APP in a Taiwanese cohort between April 2002 and February 2019. The pesticides were classified according to the Insecticide Resistance Action Committee Mode of Action (MoA) classification. The clinical characteristics, duration of hospitalization (days), follow-up duration (years), in-hospital mortality, neurological sequela, and imaging findings were recorded. Furthermore, multivariate logistic regression analyses were performed. Results: We identified 299 patients with APP comprising 206 (68.9%) adult men with a mean exposure age of 56.4 ± 16.8 years. Paraquat, organophosphates, pyrethroids, carmabates, and phosphinic acid were the most commonly known reported poisoning agents. The mortality rate was highest in users with paraquat (77.1%), followed by phosphinic acid (22.2%), carbamates (16.7%), and organophosphates (15.8%). After a mean follows up of 3.69 ± 2.26 years, the most common neurological sequela was a cognitive decline (56 among 225 survivors, 24.89%), peripheral neuropathy (11 among 225 survivors, 4.89%), tremor (10 among 225 survivors, 4.44%), ataxia (3/225, 1.33%), and parkinsonism feature (2/225, 0.89%). Brain imaging studies revealed basal ganglion lesions on CT or hyperintensity on T2-weighted MRI images in 26 among 46 patients (56.5%). The basal ganglion lesions on brain imaging had a positive correlation with neurological sequelae. Conclusion: Acute pesticide poisoning (APP)-related mortality is high especially paraquat intoxication, and cognitive decline, as well as peripheral neuropathy, were the most common neurological sequelae among survivors, which is highly correlated with basal ganglia lesions on brain imaging.